The Effect of Consumption Patterns and Physical Activity on the Incidence of Obesity in Bank Employees in Medan City - Jenita Oktavia Panjaitan; Evawany Y Aritonang; Etty Sudaryati (International Journal Labs, 2023)
Indonesia has an obesity prevalence increased from 15.4 percent in 2013 (Riskesdas 2013) to 21.8 percent in 2018 (Ministry of Health RI, 2018) and in North Sumatra, the prevalence is 25.8 percent. Meanwhile, Indonesia's target in reducing obesity is contained in the 2020-2024 RPJMN by 21.8 percent so that North Sumatra has a difference of four percent. Poor food consumption patterns such as consuming foods that are high in fat, sugar, and calories and lack of physical activity that leads to sedentary activity can cause an increase in the incidence of obesity in adults, especially in employees who are more than seven hours just sitting in front of the computer. This study aims to determine the effect of consumption patterns and physical activity on the incidence of obesity in bank employees in Medan City. This research was conducted at Bank Negara Indonesia (BNI) in Medan City in February 2023 with a case control research design. Obesity data were obtained by anthropometric measurements, consumption patterns using the Semi Quantitative Food Frequency Questionnaire and physical activity using the Physical Activity Level questionnaire. The sample size was 150 respondents, consisting of a case sample of 50 respondents and a control sample of 100 respondents. Data analysis using chi-square test and multiple logistic regression. The results of chi-square analysis showed a significant effect of energy intake (?= 0.000, OR = 6.6), carbohydrate intake (?= 0.000, OR = 11.3), protein intake (?= 0.000, OR = 4.1), fat intake (?= 0.000, OR = 4.1) and physical activity (?= 0.001, OR = 4.1) on the incidence of obesity. The frequency of consumption (?= 1,000, OR = 1,046) and the type of food (?= 1,000, OR = 0.961) showed no influence on the incidence of obesity. Multiple logistic regression tests showed that the most dominant variable influencing obesity was carbohydrate intake (?= 0.000, OR = 11.3). The conclusion of this study is that there is an influence of consumption patterns and physical activity on the incidence of obesity in bank employees in the city of Medan.